2016
DOI: 10.1111/dth.12417
|View full text |Cite
|
Sign up to set email alerts
|

Using Feily's method prevented scalp necrosis in three patients incline to the scalp recipient necrosis; what is new in prevention of scalp necrosis?

Abstract: Serious complications arising from surgical hair restoration are relatively uncommon following well-performed and well-planned surgery by skillful surgical techniques, good communication, and postoperative follow-up. Surgical complications often categorized as those which occur in the donor site and the recipient site. In this paper among recipient area complication we focused on recipient area necrosis that arises when an increased number of recipient grafts are utilized and de-vascularization of the scalp oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Follicular transplantation into regions of scalp scars is difficult. [ 1 2 ] Several reports document the underlying importance of improved local blood flow via tissue debridement or hyperbaric oxygen therapy, before performing dense hair transplantation. [ 3 ] In a previous study, we described an “ischemia timeline,” toward aiding clinicians to avoid scalp necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Follicular transplantation into regions of scalp scars is difficult. [ 1 2 ] Several reports document the underlying importance of improved local blood flow via tissue debridement or hyperbaric oxygen therapy, before performing dense hair transplantation. [ 3 ] In a previous study, we described an “ischemia timeline,” toward aiding clinicians to avoid scalp necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…An important form of cicatricial alopecia is that seen in the post-radiotherapeutic of patients with scalp, skull, or brain tumors. Unfortunately, hair transplantation in regions of secondary scarring alopecia (e.g., radiotherapy, burns, and surgery),[ 1 2 3 4 ] is similarly difficult to the transplantation of a scalp scar for similar pathophysiological reasons. Therefore, transplantation of regions of cicatricial alopecias also require careful planning, minding of the ischemia timeline, and innovative procedural techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the available literature and found that there are no official guidelines about the etiology, progression, and treatment of scalp necrosis. Morbidity is much higher in a previous study than in our clinical work, 2,10 indicating that technical improvement and good perioperative management may help to reduce this complication 11 . Herein, we reviewed cases with scalp necrosis following hair transplantation over the past decade, and focused on the pathogenesis, progression, treatment, and preoperative prevention of scalp necrosis to minimize complications and improve outcomes.…”
Section: Introductionmentioning
confidence: 87%
“…Creating a natural and dense hairline is considered one of the greatest surgical challenges [ 3 ] [ 4 ]. Novice surgical skills and subsequent patient dissatisfaction frequently result in consultation for transplant removal; laser ablation is commonly used for removal.…”
Section: Introductionmentioning
confidence: 99%